The State and the production of social conventions about the firearms market in Brazil - Vieira, Mateus Tobias [UNESP]; Jardim, Maria Chaves [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2024)
The article analyzes the role of the state in formulating social conventions about firearms in Brazil. We selected Law 10.826/2003, passed during the first Lula Government (2003–2006), as the empirical dispute, and also we analyzed eight presidential decrees from the first year of the Bolsonaro Government (2019). In the methodology, we analyzed the legal framework based on the studies of Steiner and Trespeuch, about contested markets; Bourdieu, about the state and the concept of social convention, by Mary Douglas. The results indicate that the state has influenced the production of predispositions and that the disarmamentist social convention, produced during the Lula Government, has been challenged, generating disputes that go beyond the normative perspective.
O Estado e a produção de convenções sociais acerca do mercado de armas de fogo no Brasil
Keywords: Armas de fogo; Bolsonaro Government; Contested markets; Disarmament Statute; Estatuto do Desarmamento; Firearms; Governo Bolsonaro; Governo Lula; Lula Government; Mercados contestados